THE TEACHERS’ PERSPECTIVES TOWARDS THE LITERACY PROGRAM DEVELOPED AT A BILINGUAL SCHOOL - Oktarina, Putu Santi (Yavana Bhasha : Journal of English Language Education, 2019)
There can be multiple sorts of bilingual education, they depend on how the two languages are taught, on the teaching goals and on the teachers. Moreover, it is on the pupils, methods, state policy and society's attitude towards bilingualism. Dyatmika school is an example of a bilingual school in Bali. Dyatmika School (Sekolah Dyatmika) is currently in its 17th year of operation and has grown to offer a rich educational programme in English and Indonesian to children from the age of 3 to 18. The Primary School of Dyatmika School covers classes 1 to 6 and has a dual language program of Indonesian and English. English literacy has been done for years, but intensive Indonesian literacy has just been done for a year and a half. It can be said that this bilingual literacy program has just started for 1.5 years. It is important to see the perspective of the teachers towards the bilingual literacy program run in Dyatmika School. This study used a descriptive qualitative design. The research subjects of the present study were the national teachers of Dyatmika school. The subjects were class teachers and one was a substitute teacher. Based on the research conducted, there are two main results, namely (1) there are four biliteracy programs done by Dyatmika School involving reading aloud, shared reading, guided reading, and home reading. (2) According to the local teacher’s perspective, the biliteracy program applied in Dyatmika is beneficial for the students as well as for the teachers. The correlation between both languages in which they are presenting a similar topic but in a different way make the students get a deeper understanding of the topic.